2006
DOI: 10.1111/j.1444-2906.2006.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of larval quality of viviparous scorpionfish Sebastiscus marmoratus

Abstract: Abstract:We aimed to develop an acute test for larval quality in the viviparous scorpionfish (Sebastiscus marmoratus). Rearing experiments until day 13 post parturition were conducted to investigate the survival of larvae for 13 different batches, and tolerance to starvation of larvae was examined and expressed by the survival activity index (SAI). We also observed 5 the morphological characters, enzyme activity, and swimming behavior of larvae on day 0 and 1, followed by the correlation analysis between SAI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
0
21
0
2
Order By: Relevance
“…Additionally, some studies used the enzyme activity as an indicator for assessing the fitness and survival potential of fish larvae [2,5]. Supporting evidence was found by Ueberschär [2] who reported a tryptic activity measurement is useful in detecting unfavorable health condition of herring larvae.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Additionally, some studies used the enzyme activity as an indicator for assessing the fitness and survival potential of fish larvae [2,5]. Supporting evidence was found by Ueberschär [2] who reported a tryptic activity measurement is useful in detecting unfavorable health condition of herring larvae.…”
Section: Discussionmentioning
confidence: 55%
“…Matsuo et al [5] also reported enzyme activity, esterase and alkaline phosphatase, can be a real-time index for evaluating the quality of viviparous scorpionfish larvae. Although Araujo et al [4] did not find correlation between enzyme activity and survival in Japanese flounder larvae, they observed whenever esterase and phospholipase fluorescence intensities were low, survival and growth of larvae were also low.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations